FAKTOR-FAKTOR KEPUASAN MAHASISWA SCHOOL OF MARKETING TERHADAP UNIVERSITAS BUNDA MULIA DENGAN METODE FACTOR ANALYSIS - Rudy Santosa Sudirga (Universitas Bunda Mulia, 2017)
Over the last three years the number of students choosing School of Marketing (SOM) Bunda Mulia University as a university choice has steadily increased. Studies have demonstrated that university preference at the time that students enter university may be significantly associated with their ultimate choice. The main purpose of this research is to examine the role of positive and negative affectivity variables on the relationship between optimism and satisfaction of school of marketing students to the role of bunda mulia university in providing accurate services study programs and student services. Several measurement assumptions were examined with the goal of assessing the program study lectures, validity of services, living environment, university facilities, university library, and general quality of day to day university services. Confirmatory factor an factor mixture analysis of interval data were used to examine the measurement assumptions. A correlated five-factor model for an abridged version of the factor analysis resulted in good fit when all negatively worded items and several positively worded items were excluded. The abridged item version of the factor analysis provides a promising alternative for the measurement of five factors that are pertinent to adolescents’ quality of university sevices either in program study lectures or in quality services to their students. The purpose of this paper is to explore student perceptions of study characteristics of their internships and to explore the relationship between study characteristics and overall satisfaction with their internship experiences. Bunda Mulia University may use this information to enhance the structure and tasks associated to improve university services. This paper also provides a comprehensive look and analysis of study at school of marketing and satisfaction analysis, as they related to satisfaction in an internship environment. In addition, lecturers’ academic qualifications tends to lead to a mismatch between students’ expectations and professional realities, therefore reduces students’ study satisfaction. Primary findings indicate that there is significant cause and effect on the adolescents’ satisfaction with their interpersonal relationships between their life and the virtual world. Social aspects also affect positive organizational outcomes, specifically positive word-of-mouth in society and community.